Modeling in yeast how rDNA introns slow growth and increase desiccation tolerance in lichens - Daniele Armaleo; Lilly Chiou (G3: Genes, Genomes, Genetics, 2021)
AbstractWe connect ribosome biogenesis to desiccation tolerance in lichens, widespread symbioses between specialized fungi (mycobionts) and unicellular phototrophs. We test whether the introns present in the nuclear ribosomal DNA of lichen mycobionts contribute to their anhydrobiosis. Self-splicing introns are found in the rDNA of several eukaryotic microorganisms, but most introns populating lichen rDNA are unable to self-splice, being either catalytically impaired group I introns, or spliceosomal introns ectopically present in rDNA. Although the mycobiont’s splicing machinery removes all introns from rRNA, Northern analysis indicates delayed post-transcriptional removal during rRNA processing, suggesting interference with ribosome assembly. To study the effects of lichen introns in a model system, we used CRISPR to introduce a spliceosomal rDNA intron from the lichen fungus Cladonia grayiSaccharomyces cerevisiae